The future of work: the meaning and value of work in Europe - Méda, Dominique (Geneva, 2016)
"This paper looks at the notion of work historically and how new meanings have enriched this notion over centuries. It then analyses the importance Europeans give to the concept of work, and presents the ongoing discourse on technological revolution and its impact on work and employment. The paper then examines the future of work in the coming decades in the light of three broad scenarios, which are competing to present a mid-term view of the future of work. First, the consequences of a scenario called “dismantling the labour law” are considered. Second, the validity of the propositions announcing the end of work within the scope of automation and digitalization (scenario of the technological revolution) are examined. Finally, a third scenario, the “ecological conversion”, which seems to be the most compatible with the need to combat the unbearable features of our present model of development and seems capable of satisfying the expectations placed on work is examined. It is this third scenario – “ecological conversion” – that seems best able to respond to the high expectations that Europeans continue to place on work while ensuring the continuation of our societies."